RETRACTED: Spiking Correlation Analysis of Synchronous Spikes Evoked by Acupuncture Mechanical Stimulus - Qin, Qing; Liu, Ya-Jiao; Shan, Bo-Nan; Che, Yan-Qiu; Han, Chun-Xiao; Qin, Ying-Mei; Wang, Jiang (Frontiers in Computational Neuroscience, 2020)
Acupuncturing ST36 acupoint can evoke the response of the sensory nervous system, which is translated into output electrical signals in spinal dorsal root. Neural response activities, especially synchronous spike events, evoked by different acupuncture manipulations have remarkable differences. In order to identify these network collaborative activities, we analyze the underlying spike correlation in the synchronous spike event. In this paper, we adopt a log-linear model to describe network response activities evoked by different acupuncture manipulations. Then the state-space model and Bayesian theory are used to estimate network spike correlations. Two sets of simulation data are used to test the effectiveness of the estimation algorithm and the model goodness-of-fit. In addition, simulation data are also used analyze the relationship between spike correlations and synchronous spike events. Finally, we use this method to identify network spike correlations evoked by four different acupuncture manipulations. Results show that reinforcing manipulations (twirling reinforcing and lifting-thrusting reinforcing) can evoke the third-order spike correlation but reducing manipulations (twirling reducing and lifting-thrusting reducing) can’t. This is the main reason why synchronous spikes evoked by reinforcing manipulations are more than reducing manipulations.